2020
DOI: 10.3390/agronomy10091261
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Raffia as a Sustainable and Cost-Effective Alternative to Improve the Management of Agricultural Waste Biomass

Abstract: The transition from intensive conventional agriculture to sustainable agriculture has become a global priority. This is due to the need for environmentally friendly agriculture to ensure sufficient food for a rapidly growing population. The bioeconomy is essential to progress in the field of sustainable agriculture. It contributes to the conservation of biological resources through circular and comprehensive management. The bioeconomy prioritizes the reduction and reuse of materials and products. The focus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…It is present in the covering and natural ventilation systems of greenhouses, irrigation equipment and active climate control, agricultural inputs and disinfection processes. It is also used in auxiliary structures such as irrigation ponds and the marketing of the goods [18,22,[59][60][61][63][64][65][66][67][70][71][72]. The determination of the generation period of this tyspe of waste is established by the crop cycles with a productive seasonality due to their intrinsic characteristics [73,74] Specifically, it was estimated that around 90% of agricultural plastic waste is generated in the province of Almeria between August and September [18].…”
Section: Characterization and Estimation Of The Production Of Agricultural Plastic Waste In The Productive Sector Of Greenhouse Agricultumentioning
confidence: 99%
See 2 more Smart Citations
“…It is present in the covering and natural ventilation systems of greenhouses, irrigation equipment and active climate control, agricultural inputs and disinfection processes. It is also used in auxiliary structures such as irrigation ponds and the marketing of the goods [18,22,[59][60][61][63][64][65][66][67][70][71][72]. The determination of the generation period of this tyspe of waste is established by the crop cycles with a productive seasonality due to their intrinsic characteristics [73,74] Specifically, it was estimated that around 90% of agricultural plastic waste is generated in the province of Almeria between August and September [18].…”
Section: Characterization and Estimation Of The Production Of Agricultural Plastic Waste In The Productive Sector Of Greenhouse Agricultumentioning
confidence: 99%
“…Unfortunately, their technological limitation only allows their use in a few productive activities, mainly to replace traditional composts in mulching and mulching raffias. Its characteristics enable it to withstand production cycles of up to nine months, which makes it an ideal replacement for mulching used throughout the crop cycle [59,65,66,69]. Other types of biodegradable mulching, such as straw or rice husks, could also be used [68,69].…”
Section: Opportunities For Waste Management and Use Of Plastic By-products By The Different Agents Involved: Inclusion In The Cementioning
confidence: 99%
See 1 more Smart Citation
“…The circular economy (CE) and the bioeconomy (BE) have become alternative economic production models (EPMs) that are essential to promote sustainable growth and development [ 1 , 2 , 3 ]. The main goal of both models is to achieve a synergy between the economy, the environment, and society [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technological innovations are fine, but without the presence of strong symbiotic relationships among players in a circular bio-economy, they would not be able to deliver the goods. The reference here is to bottom-up initiatives which resulted in the success of the agro-industrial complex in the Almeira region of Spain which is making good use of the opportunity to become an integral part of a sustainable circular bioeconomy, by recognising the resource potential of the horticultural residues generated [33,49,170,379]. On the other hand, in a historical analysis of the complex nexus among landscape, livestock, farming population and land uses in the agrarian metabolism in Barcelona, researchers have concluded that there has been a conspicuous decrease in circularity over time [146], which needs to be restored.…”
Section: Discussion-systematic Reviewmentioning
confidence: 99%